Unearthing Hazards: Investigating the Root Causes of Workplace Accidents at PT Indo Muro Kencana's Gold Mines - Pranitasari, Diah; Arfi Alfarius (Jurnal Ecoment Global, 2023)
Objective: This study seeks to dissect the occurrences of work-related accidents at PT Indo Muro Kencana (PT IMK) over a period spanning from 2018 to 2023. It aims to pinpoint the contributing factors to these mishaps, analyzing them to forge actionable recommendations and preventive strategies aimed at mitigating accident risks and enhancing workplace safety and health. Design/Methods/Approach: Employing a quantitative descriptive methodology, this research adopts an observational descriptive design to catalog and scrutinize work accident incidents. The Loss Causation Model serves as the analytical framework, facilitating a thorough evaluation of accident causatives. The study encompasses all PT IMK employees during the specified timeframe, utilizing a total sampling approach. Data compilation hinges on secondary sources, including company accident reports and relevant literature, with SPSS Statistics 25 software facilitating cross tabulation for data analysis. Findings: Analysis reveals a fluctuating pattern of work accidents over the years, with a significant portion resulting from direct physical interactions such as collisions and strikes. Predominantly occurring in excavation and roadway sectors, these incidents frequently involve heavy machinery and service vehicles. Notably, accidents disproportionately affect younger employees with limited tenure, though veterans are not exempt from risk. Primary accident triggers are identified as unsafe acts—including procedural breaches and poor decision-making—and unsafe conditions like slippery surfaces and subpar equipment. Underlying causes are attributed to human elements, notably inadequate judgment skills, and occupational hazards, including poor hazard awareness and deficient job safety analysis. Originality/Value: This research pioneers in its focused examination of work accident causatives within PT Indo Muro Kencana's gold mining operations, marking a novel contribution to occupational safety and health literature in the mining sector. Practical/Policy implication: The insights garnered herein are poised to inform the development of targeted safety programs, underlining the study's utility in propelling occupational safety and health consciousness, alongside facilitating accident risk reduction initiatives.